2014
DOI: 10.4401/ag-6237
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Environmental Seismic Intensity scale (ESI 2007) and the European Macroseismic Scale (EMS-98) to the Kalamata (SW Peloponnese, Greece) earthquake (Ms=6.2, September 13, 1986) and correlation with neotectonic structures and active faults

Abstract: On September 13, 1986, a shallow earthquake (Ms=6.2) struck the city of Kalamata and the surrounding areas (SW Peloponnese, Greece) resulting in 20 fatalities, over 300 injuries, extensive structural damage and many earthquake environmental effects (EEE). The main shock was followed by several aftershocks, the strongest of which occurred two days later (Ms=5.4). The EEE induced by the 1986 Kalamata earthquake sequence include ground subsidence, seismic faults, seismic fractures, rockfalls and hydrological anom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…As regards the western and southern Peloponnese, onshore and offshore studies revealed that it is composed of megahorsts and megagrabens bounded by N-S-and E-W-trending active fault zones and seismogenic faults [84,85,[91][92][93][94][95][96]. Offshore studies conducted in the Kyparissia [96], Messenian [97] and Laconian [98] Gulfs demonstrated that active faults observed onshore in the study area continue in several cases offshore.…”
Section: Geological Settingmentioning
confidence: 99%
“…As regards the western and southern Peloponnese, onshore and offshore studies revealed that it is composed of megahorsts and megagrabens bounded by N-S-and E-W-trending active fault zones and seismogenic faults [84,85,[91][92][93][94][95][96]. Offshore studies conducted in the Kyparissia [96], Messenian [97] and Laconian [98] Gulfs demonstrated that active faults observed onshore in the study area continue in several cases offshore.…”
Section: Geological Settingmentioning
confidence: 99%